ادارة السمعة الرقمية لوكالة الاتصال الجزائرية - الادريسي, آية كوثر (كلية العلوم الاجتماعية, 2023)
تناولت الدراسة موضوع بناء السمعة الرقمية في الوكالات الاتصالية عبر مواقع التواصل الاجتماعي، وقد تم اختيار صفحة الوكالة الاتصالية وليد يطو على الفيسبوك، مؤسسة اتصالية رقمية تقدم خدمات متنوعة، فكان لابد من التعرف على كيفية بناء السمعة الرقمية عبر موقع الفيسبوك من خلال عينة احتمالية قصدية من منشورات الصفحة المتمثلة في مجموعة من الخدمات التي تم تحليلها مضمونًا بالنسبة للمواضيع، الأهداف، الجمهور المستهدف، الاتجاه، ومصدر المعلومة، وشكلًا من خلال شكل قالب المضمون، زمن النشر، اللغة المستخدمة، والتصميم، اما تفاعليًا فتم دراسة رد فعل الجمهور، التعليقات، تداول النشر والمشاركة. اعتمدنا في الدراسة على المنهج الوصفي التحليلي بأسلوب المسح الاجتماعي باستخدام تحليل المضمون كأداة للدراسة، من اجل وصف وتحليل طريقة النشر التي تعتمدها الوكالة، وذلك للإجابة عن الاشكال التالي: كيف تبني وكالة اتصال "وليد يطو" سمعتها الرقمية عبر صفحتها على الفيسبوك؟ وقد طرحنا مجموعة من الأسئلة الفرعية المدعمة للسؤال الرئيسي من بينها: ماهي اشكال المضامين التي تستخدمها وكالة الاتصال في نشرها عبر صفحة الفيسبوك؟، ماهي الآليات التي تعتمدها وكالة اتصال وليد يطو لتحسين صورتها الرقمية؟ اما بالنسبة للجانب التطبيقي درسنا ستة منشورات باستخدام تحليل المضمون، حللنا فئات الشكل والمضمون للعينة بهدف معرفة كيفية استخدام المواضيع، الألوان، والاشكال في بناء السمعة الرقمية، بحيث توصلنا من خلال ذلك الى النتائج التالية: - الاعتماد على أساليب حديثة في المنشورات من اجل بناء سمعة رقمية لمؤسسة وليد يطو. - نشر مؤسسة وليد يطو الخدمات في شكل صور وفيديوهات حقيقية لإثبات مصداقية المؤسسة في نوعية المنتج والخدمة التي تقدمها من اجل بناء سمعة رقمية جيدة. - يظهر تفاعل الجمهور الإيجابي على نوعية خدمات مؤسسة وليد يطو مما يؤكد على بناء سمعة رقمية جيدة لها الكلمات المفتاحية : السمعة الرقمية - مواقع التواصل الاجتماعي- وكالة اتصال - موقع الفيسبوك Abstract : The study dealt with the issue of building a digital reputation in communication agencies through social networking sites. Walid Yettou Facebook page for the communication agency was selected as a digital communication institution that provides various services. The page publications represented in a set of services that were analyzed in terms of content, objectives, target audience, direction, and source of information, and in form through the form of the content template, publishing time, language used, and design. Interactively, the audience reaction, comments, circulation were studied. Publish and share. In the study, we relied on the analytical descriptive approach using the social survey method, using content analysis as a tool for the study, in order to describe and analyze the publishing method adopted by the agency, in order to answer the following questions: How does the communication agency "Walid Yettou" build its digital reputation through its Facebook page? We have asked a set of sub-questions that support the main question, including: What are the forms of content that the communication agency uses to publish it on the Facebook page? What are the mechanisms adopted by Walid Yato's communication agency to improve its digital image? As for the applied side, we studied six publications using content analysis. We analyzed the categories of form and content of the sample in order to know how to use topics, colors, and forms in building a digital reputation, so that we reached the following results: - Relying on modern methods in publications in order to build a digital reputation for the Walid Yato Foundation. Walid Yatto Foundation publishes services in the form of real photos and videos to prove the institution's credibility in the quality of the product and service it provides in order to build a good digital reputation. - The positive public interaction appears on the quality of Walid Yettou Foundation's services, which confirms the building of a good digital reputation for it. key words : Digital reputation - social networking sites - communication agency - Facebook
دراسة تحليلية لمضمون صفحة فيسبوك وكالة _وليد يطو_
Keywords: السمعة الرقمية - مواقع التواصل الاجتماعي- وكالة اتصال - موقع الفيسبوك Digital reputation - social networking sites - communication agency - Facebook